Efeito da aplicação de vibração mecânica localizada durante o treinamento de força sobre a hipertrofia muscular - Marcos Daniel Motta Drummond (2012)
Several studies indicate that the addition of vibrations to the strength training (ST) may contribute to the development of muscle strength and athletic performance. The aim of this study was to verify the chronic effect of application of mechanical vibration during ST on muscle hypertrophy. The sample consisted of 20 male volunteers, mean age 21,3 ± 3,02 years in the group trained without vibration and 21,1 ± 2,13 years in the group trained with vibration. All volunteers were untrained. Initially, all volunteers underwent magnetic resonance imaging to determine the cross-sectional area of the elbow flexors, and strength tests of one repetition maximum (1RM) and maximal voluntary contraction (MVC). Later, the volunteers were divided into two groups: one group with the addition of located mechanical vibration in the training protocol (GCV) and another without the addition of mechanical vibration (GSV). Both groups performed ST for hypertrophy of the elbow flexor muscles for 12 weeks. The ST protocol consisted of performance four sets of eight to 10 repetitions maximum, of the exercise unilateral elbow flexion in the Scott bank. The intervals between sets were 120 seconds and the frequency ofthree weekly sessions. The GCV performed the same training protocol, but with the addition of the mechanical vibration frequency of 30 Hz and the amplitude of 6 mm. After the training period both groups had significant increases in muscle strength, from the results of 1RM tests and CVM. There was no significant difference between the strength gains made by groups. In magnetic resonance imaging was found significant hypertrophy of the elbow flexors in both groups. Muscle hypertrophy was similar in the groups. Therefore, the application of vibration did not alter the results of the dynamic force training.